Self-Assembled KLD-12/SDF-1 Polypeptide Promotes Differentiation and Migration of BMSCs via the Wnt/β-catenin Signaling Pathways - Cao, Mingyu; Hu, Yabin; Zhang, Yukun; Xie, Jiang; Xie, Zengru (Protein and Peptide Letters, 2022)
Objective: This study aimed to evaluate the combination of SDF-1 and KLD-12 to form self-assembling polypeptide and its effect on osteogenic differentiation. Methods: ELISA assay was performed to detect whether KLD-12 composite SDF-1 self-assembled polypeptide was successfully prepared. BMSCs were isolated and characterized by Flow cytometry. MTT assays, Calcein-AM/PI fluorescence staining, and Glycosaminoglycans (GAGs) measurement were carried out to detect cell viability after cells exposed to KLD-12 composite SDF-1 selfassembled polypeptide. The migration of cells induced by KLD-12 composite SDF-1 selfassembled polypeptide was also examined by transwell assay and Immunoblot. Osteogenic differentiation of cells stimulated with KLD-12 composite SDF-1 self-assembled polypeptide was analyzed by Immunoblot, Alizarin Red Staining, and Alkaline Phosphatase activity. Additionally, immunoblot and immunofluorescence assays were performed to investigate the effects of the polypeptide on the Wnt/β-catenin pathway. Results: KLD-12 composite SDF-1 self-assembled polypeptide was successfully prepared and identified. In addition, we isolated and characterized mouse mesenchymal stem BMSCs. Our data further revealed that KLD-12 combined with SDF-1 self-assembled polypeptide improved the survival of BMSCs and promoted cell migration. Moreover, the self-assembled polypeptide induced osteogenic differentiation of BMSCs. Mechanically, we found that the self-assembled polypeptide activated the Wnt/β-catenin pathway, therefore promoting the differentiation and migration of BMSCs. Conclusion: Our proposed treatment can potentially be effective for bone defects.
Keywords: Bone defects